Connections between Ethical Values, the Meaning of Human Life, and Human Communities, according to Vasile Goldiș - IOVAN, Marțian (Journal of Legal Studies, 2017)
The author presents the views held by Vasile Goldiș – Transylvanian scholar, politician, and one of the masterminds of the Great Union of 1 December 1918 – regarding the role of universal human values in guiding individuals and human communities. Together with other Christian values, ethics guides individuals, communities, political and administrative elites, churches, and academia. This results in greater justice, community solidarity and cohesion, and a greater ability for society to shape and promote its internal moral order. Considering the diversity of moral profiles found among various nations, ethnicities and political elites, Goldiș highlights their common grounds – which facilitates a new moral order in inter-human, inter-community and international relations. The ethical testament promoted by Goldiș in his writings and throughout his life is still relevant today, and it also holds true for the next generations.